Emerging Antibiotic Resistance Patterns in a Neonatal Intensive Care Unit in Pune, India: A 2-Year Retrospective Study - Mubashir Hassan Shah; Samuel McAleese; Sandeep Kadam; Tushar Parikh; Umesh Vaidya; Sonali Sanghavi; Julia Johnson; Julia Johnson (Frontiers Media S.A., 2022)
Objective:Treating neonatal bloodstream infections and meningitis in South Asia remains difficult given high rates of antimicrobial resistance (AMR). To evaluate changing epidemiology of neonatal infections, we assessed pathogen-specific and clinical features of culture-proven infections in neonates admitted to a neonatal intensive care unit (NICU) in Pune, India.Materials and MethodsThis retrospective cohort study was performed in the King Edward Memorial Hospital and Research Center NICU over 2 years between January 1, 2017 and December 31, 2018. We included all neonates admitted to the NICU with positive blood or cerebrospinal fluid cultures. Demographic, clinical, and microbiologic data were collected from the medical record. We reviewed antimicrobial susceptibility testing (AST) of all isolates.ResultsThere were 93 culture-positive infections in 83 neonates, including 11 cases of meningitis. Fifteen (18%) neonates died. Gram-negative pathogens predominated (85%) and AST showed 74% resistance to aminoglycosides, 95% resistance to third/fourth generation cephalosporins, and 56% resistance to carbapenems. Resistance to colistin was present in 30% of Klebsiella pneumoniae isolates. Birth weight <1,000 g [odds ratio (OR) 6.0, p < 0.002], invasive respiratory support (OR 7.7, p = 0.001), and antibiotics at the time of culture (OR 4.2, p = 0.019) were associated with increased risk of mortality. Rates of AMR to all major antibiotic classes were similar between early onset and late onset infections. There was no association between carbapenem resistance and mortality.ConclusionIn our NICU in India, there are high rates of AMR among Gram-negative pathogens that are predominantly responsible for infections. Given higher colistin resistance in this cohort than previously reported, hospitals should consider routinely testing for colistin resistance.